CD44v9 Induces Stem Cell-Like Phenotypes in Human Cholangiocarcinoma - Suwannakul, Nattawan; Ma, Ning; Midorikawa, Kaoru; Oikawa, Shinji; Kobayashi, Hatasu; He, Feng; Kawanishi, Shosuke; Murata, Mariko (Frontiers in Cell and Developmental Biology, 2020)
Background Our previous study demonstrated an overexpression of CD44 variant 9 (CD44v9) in human cholangiocarcinoma (CCA) tissues that was associated with inflammation-related tumor development. However, the participation of CD44v9 in cholangiocarcinogenesis remains poorly understood. Therefore, in this study, we examined the potential roles of CD44v9 in CCA cells to understand the carcinogenic mechanism. Methods Using normal cholangiocytes (MMNK1) and CCA cells (KKU213), the expression levels of CD44v9 and its related molecules were quantified through RT-qPCR and immunocytochemical (ICC) staining. To evaluate its biological functions, we performed CD44v9 (exon 13) silencing using siRNA transfection, and assessed cell proliferation through MTT assay, cell migration, and invasion by transwell technique, and carried out cell cycle analysis by flow cytometry. In vivo tumor growth was assessed by nude mouse xenografts, and histological and molecular changes were determined using and immunohistochemical (IHC) staining. Results KKU213 exhibited higher protein expression levels of CD44v9 than those of MMNK1 through ICC staining. RT-qPCR analysis revealed that the mRNA expression level of CD44v9 was predominantly elevated in CCA cells along with its neighboring exons such as variant 8 and 10, minimally affecting the standard form of CD44. CD44v9 silencing could regulate redox system in CCA cells by reducing the expression levels of SOD3 and cysteine transporter xCT. CD44v9 silencing suppressed the CCA cell proliferation by induction of apoptosis and cell cycle arrest. Migration and invasion were decreased in CD44v9 siRNA-treated CCA cells. CD44v9 downregulation inhibited CCA tumor growth in mouse xenografts. IHC analysis demonstrated the histological changes in xenograft tissues such as an increase in connective tissues through collagen deposition and reduction of hyaluronic acid synthesis through CD44v9 silencing. CD44v9 knockdown in vitro and in vivo increased E-cadherin and reduced vimentin expression levels, resulting in reduction of epithelial-mesenchymal transition (EMT) process. Moreover, CD44v9 modulated Wnt10a and β-catenin in tumorigenesis. Conclusions Our results indicate that CD44v9 plays a potential role in CCA development by the regulation of cell proliferation and redox balancing. CD44v9 silencing may suppress tumor growth, migration and invasion through Wnt/β-catenin signaling and EMT: a finding that could potentially be applied in the development of targeted cancer therapy.